Teacher education communities of practice: More than a culture of collaboration - Patton, Kevin; Parker, Melissa (Teaching and Teacher Education, 2017)
Teacher educator professional learning, like teacher education, can be messy and complex. This study's purpose was to explore physical education teacher educators' understandings of how their participation in communities of practice (CoP) supported their own professional development. More specifically, significant dynamics and group processes of CoP were explored. Results indicated that engagement in CoP provided a foundation for collaboration and reduced isolation, allowing participants to extend teaching and research capacities. Significant social dynamics and group processes that shaped their practice included a common focus, personal and professional relationships, safe but challenging spaces, and shared commitment.
Keywords: Communities of practice; Physical education teacher education; Professional development; Professional learning; Teacher education